2011
DOI: 10.1007/s11434-010-4112-5
|View full text |Cite
|
Sign up to set email alerts
|

Study on the hyperspectral polarized reflection characteristics of oil slicks on sea surfaces

Abstract: This study is concerned with the need for remote sensing techniques for the monitoring of oil-slick pollution on sea surfaces and the effects of oil-slick pollution on the sea. We used Daqing crude oil, Jilin crude oil, heavy oil and seawater from Dalian Bay to simulate oil-slick pollution on the sea surface and obtained multi-angle hyperspectral polarized reflectance information, from which we calculated the polarization for different kinds of crude oil, and oil-slicks of different thicknesses. By comparing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The spectra of very thick oil spills exhibited poor reflection when compared with the other types of oil spills; the thin oil spills showed high reflectance. This study suggests that the spectral bands 3 and 4 of MSI are best to use for image processing and discriminate oil spills [ 19 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ]. The spectral bands acquired in these wavelengths by other satellites can also discriminate oil spills.…”
Section: Details Of Methodsmentioning
confidence: 99%
“…The spectra of very thick oil spills exhibited poor reflection when compared with the other types of oil spills; the thin oil spills showed high reflectance. This study suggests that the spectral bands 3 and 4 of MSI are best to use for image processing and discriminate oil spills [ 19 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ]. The spectral bands acquired in these wavelengths by other satellites can also discriminate oil spills.…”
Section: Details Of Methodsmentioning
confidence: 99%
“…A potential method of improving the classification model and applying it with coarser hyperspectral data would be a remote sensing data fusion approach that combines reflectance spectra with polarization imaging. Since the polarization characteristics of oil surface are able to reveal more information about the roughness and texture than using reflectance spectra along [41], they have been applied to the field of oil spill detection [42]- [44]. Therefore, we envision a fusion approach which may be able to distinguish between different types of oil that have similar reflectance spectra, and achieve accurate classification using hyperspectral data with coarser bands.…”
Section: Conclusion and Future Studymentioning
confidence: 99%
“…Sun et al studied oils in the laboratory and found that there was a polarization difference between oils and water [104]. This peaked at a look angle of 20 to 30 degrees and at the wavelength of 785 to 880 nm.…”
Section: Other Techniquesmentioning
confidence: 99%